PENENTUAN JALUR ALTERNATIF EVAKUASI BENCANA KEBAKARAN DENGAN METODE GIS BERBASIS MASYARAKAT DI RW 14 KELURAHAN SEKELOA KOTA BANDUNG - Amilia Widya; Selfa Septiani Aulia; Rino Adibowo; Nadya Nanda Prawila (Indonesian Community Service and Empowerment Journal (IComSE), 2026)
Fire is one of the disasters that often occurs in the city of Bandung. Based on data from the Bandung City Fire and Disaster Management Service (Diskar PB), in 2023, one of the houses in RT 05 RW 14, Sekeloa Village, experienced a fire. Areas prone to fire require solutions to this problem. The stages of the Disaster Management Cycle in the Pre-Disaster phase can be carried out through determining evacuation routes, socializing about prevention and determining assembly points. The method for implementing P2M uses the Participatory Rural Appraisal (PRA) method, namely in RW 14, fire socialization was carried out, followed by participatory mapping of disaster evacuation routes and assembly points. The results revealed 16 evacuation routes and three assembly points. A focus group discussion (FGD) was held to disseminate information on fire evacuation route standards based on Government Regulation No. 15 of 2016, as well as a discussion on the roles of the government and community in addressing obstacles in disaster evacuation routes to ensure they remain functional. Pre-test and post-test measurements to measure the understanding of the community in RW 14 regarding disaster mitigation through reducing vulnerability by determining disaster evacuation routes. FGD participants were 65% male and 35% female. The age range of FGD participants was 36-52 years. Based on the analysis results, there was an increase in the understanding of the RW 14 community regarding fire disaster mitigation through reducing vulnerability and determining disaster evacuation routes in a participatory manner. During the pre-test, the understanding score of the RW 14 community was 62.18% and increased to 73.72% during the post-test. Key words: Socialitation, Disaster, Evacuation Route, Assembly Point, Participatory Rural Appraisal (PRA)